The Effect of Coffee Consumption on Blood Sugar Levels in Diabetes Mellitus Patients in the Working Area of West Denpasar Puskesmas II, Denpasar, Bali, Indonesia - Putu Sulistiawati; I Ketut Gama; Ketut Sudiantara; I Gusti Ketut Gede Ngurah (Knowledge Dynamics, 2024)
Background: Non-communicable diseases (NCDs) are chronic diseases that cannot be transmitted from person to person. The aim of this study was to determine the effect of coffee consumption on blood sugar levels in diabetes mellitus sufferers in the West Denpasar Health Center II Working Area, Denpasar City. Methods: This research method uses pre-experimental design using a non-equivalent control-group before-after design. The research subjects were diabetes mellitus sufferers aged 45 years and over. The population in this study was 77 and the total sample for this study was 44 people using the non-probability sampling technique with the purposive sampling method. The data collection instrument uses a glucometer. Coffee is consumed twice/day as much as 200 ml in the morning and evening 5 minutes after eating for 6 days. Results: The research results showed that of the 44 respondents, in the treatment group it was found that the average blood sugar level before being given coffee was 183.50 mg/dL, and after being given coffee was 168.50 mg/dL. Meanwhile, in the control group, the average blood sugar level before and after the study was 198.50 mg/dL. The results of univariate analysis used the Wilcoxon test and obtained a p value of 0.000 (α < (0.05)). Conclusion: The conclusion of this research is that there is an effect of drinking coffee on blood sugar levels in diabetes mellitus sufferers in the West Denpasar Health Center II Working Area, Denpasar City. It is hoped that from the results of this research, drinking coffee can be used as an alternative drink to lower blood sugar levels.